Teologi Salib dalam St. John Passion: Kristus Dimuliakan Melalui PenderitaanNya - Maria Stefany (VERBUM CHRISTI JURNAL TEOLOGI REFORMED INJILI, 2020)
In this article, the author provides an introduction to the importance of great musical works for the Christian faith—in which music and theology can be integrated; and through music, theology can be articulated. However, the author points out the gap between the writings of musicologists and theologians with the Christians’ life today. In this research, the author focused on St. John Passion by Bach—in which many Christians can actually enjoy his music, but their understanding of this work is very limited. In the discussion, the author describes the work of St. John Passion—based on Johannine’s view and the theology of the cross which it contains; and answers the questions: (1) How can through a great musical work, the theology of the cross—Christ glorified through His suffering—can be articulated? (2) How can Christians put their faith in the Savior who was humiliated, suffered, and humbled to the deepest lowliness?